Analysis and Optimization of Dysprosium-Doped Yellow Fiber Lasers for Ophthalmology Applications - Foroogh Khozeymeh; Federica Poli; Wahida Chowdhury; Annamaria Cucinotta (IEEE Photonics Journal, 2024)
In this paper, a Forward Time Centered Space (FTCS) method and an analytical method have been developed to fully investigate the $^{4}F_{9/2}$ to $^{6}H_{13/2}$ lasing transition of a dysprosium Dy $-$ doped ZBLAN fiber which provides the potential of highly efficient yellow laser direct generation. This light source is of significant interest for treating diabetic retinopathy, which can cause blindness. The developed method's validity is confirmed through the comparison with experimental investigations of Dy $-$ doped ZBLAN fiber lasers in other valid research. A full analysis of Dy $-$ doped fiber laser including the population of the energy levels, power evolution of the laser and pump signals, amplified spontaneous emission (ASE), excited state absorption (ESA), radiative and non-radiative time transition rates are presented. The developed numerical method gives a better understanding of the impact of ASE and ESA on laser performance. The influence of overlap integrals, output mirror reflectivity, and active fiber length on laser performance is investigated. The optimization criteria based on the different robust configurations of laser cavities are found which predict the slope efficiencies higher than half of the Stokes limit.